The Role and Content of Lectures in the System of Higher Education - I.I. Yulchiev (Genius Journals, 2022)
This article provides recommendations on the organization and conduct of lectures in a meaningful and interesting way and discusses the role of lectures in the higher education system. In addition, in the course of lectures, methods of organizing creative didactic games and competitions among students, the essence of this method and the results of these methods were also covered
Keywords: didactic issue; rational organization; synopsis; didactic purpose